Detection of apoptosis mechanism on renal cancer cell treated by 16,17-dehydrodeacetyl-5α-oleandrin compound isolated from Nerium indicum Mill. Leaves. - Mae S.H. Wahyuningnsih; Sofia Mubarika; Ibnu G. Gandjar; Subagus Wahyuono; AWM. Boersma; K. Nooter (Indonesian Journal of Pharmacy, 2008)
The 16,17-dehydrodeacetyl-5α-oleandrin was isolated from an active fraction of Nerium indicum Mill leaves (fam. Apocynaceae). This compound was cytotoxic against various cancer cells, and selective on A498 cells (Renal cancer). However, the apoptosis mechanism was still unknown yet. Therefore, the aim of this study was to know the apoptotic mechanism of 16,17-dehydrodeacetyl-5α-oleandrin on A498 cells by FITC labeled annexin V and immunucytochemical assays. The detection of apoptotic mechanism on A498 cells was performed with FITC-conjugated annexin V using Flow Cytometry. The p53 protein expression were detected using immunocytochemical. Treatment with 16,17-hydrodeacetyl-5α-oleandrin (3.88 x 10-4 mM) using FITC-annexin V increased the percentage of the dead cells in the 24th and 48th hours incubation period. The 16,17-dehydrodeacetyl-5α-oleandrin (1,94x10-4 and 3,88x10-4 mM) raised significanly p53 protein expression (p<0,05). The percentage of the p53 protein expression increased throughout the time of samples incubation.Key words: 16,17-dehydrodeacetyl-5α-oleandrin,fluorescein isothiocyanate-annexin V, immunocytochemically, A498 cells.